PENGARUH INVENTARISASI DAN LEGAL AUDIT TERHADAP OPTIMALISASI PEMANFAATAN BARANG MILIK DAERAH DENGAN KUALITAS APARATUR SEBAGAI VARIABEL MODERASI PADA PEMERINTAH KOTA BANDA ACEH - Rizqina, Tania Indira; Nadirsyah, Nadirsyah (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2021)
The objective of this research is to analyse the impact of stocktaking and legal auditing to the optimization of aset utilization and human resource quality as moderating variable at Local Government of Banda Aceh. The Variable Utilised for this research are stocktaking, legal auditing and human resources. Respondent were selected through sensus. This is a quantitative research and the method used was multiple regression analysis. The research finding shows that, the stocktaking have impact to the optimization of aset utilization; while the legal auditing has no impact toward the optimization of aset utilization. Human resources quality have impact to the relation between stoctaking and the optimization of asset utilization, but human resource has no impact to relation between legal auditing and optimization of aset utilization.